Exploring Islamic Educational Values in the Padungku Tradition of Molowagu - Zulham; Rusdin; Andi Anirah (Journal of Contemporary Islamic Education, 2025)
The Padungku tradition in Molowagu Village is an expression of gratitude for the harvest as well as a reinforcement of social solidarity. Modernization shifts its meaning, so this study emphasizes its function as a medium for internalizing religious values, social ethics, and communal cohesion in contemporary empirical society. This study aims to analyze the values ​​of Islamic Education contained in the Padungku tradition and explain the role of this tradition in shaping religious awareness of social solidarity and religious education practices in the Molowagu Village community, Batudaka District, Tojo Una Una Regency. The study uses a qualitative approach with an ethnographic research type. Data were obtained through observation, interviews, and documentation, then analyzed descriptively interpretatively with triangulation of sources and techniques to ensure data validity. The results show that the Padungku Tradition of the Pamona Poso community is a socio-historical construction since the seventeenth century that integrates the relationship between humans, nature, and God and transforms through Islamization without losing local identity. Ethnographically, this tradition internalizes the values ​​of gratitude, social solidarity, and collective ecological awareness. The implications of this research confirm that the integration of local wisdom in Islamic education contributes to enriching the development of culture-based education while strengthening the function of tradition as a medium for contextual socio-religious education in community life